INCREASED LEVEL OF MIR-204-5P EXPRESSION IN MELANOMA CELLS UNDER THE INFLUENCE OF DACARBAZINE - S. N. Lavrentiev; M. B. Aksenenko; A. S. Averchuk; A. V. Komina; N. V. Palkina; T. G. Ruksha (Сибирский онкологический журнал, 2019)
Various types of tissues was analyzed, and the algorithm for summing neutron and photon doses in neutronMiRNA s are involved in the regulation of numerous critical biological processes, including cell proliferation, differentiation, migration and invasion. They function as oncogenes or tumor suppressors according to the nature of the target. It has been previously determined that miR-204-5p miRNA is characterized by the increased level in melanoma. The aim of this study was to determine the effects of changes in the level of microRNA expression when dacarbazine was exposed to melanoma cells in vitro and synthetic miR-204-5p in vivo. The expression levels of miR-204-5p and miR-211 in melanoma cells were determined by real-time PCR. Antitumor effects in vivo were verified in assessing the growth dynamics of the tumor node. Toxic effects were assessed by animal behavior, fluid intake, feed, and ALT , AST , creatinine, urea levels. In the model of melanoma C57BL6, it was revealed that the introduction of the synthetic miR-204-5p did not cause significant changes in the investigated microRNA in tumor cells. At the same time, the antitumor effects of dacarbazine in melanoma cells in vitro led to an increase in the level of the investigated microRNA by more than 20 times. The results of the study indicated the possibility of compensating the level of miR-204-5p under the influence of cytostatic therapy. Taking into account the previously revealed miR-204-5p inhibitory effect on the proliferation of melanoma cells, we can assume that this miRNA can play a role in maintaining the dermal state of tumor cells. Further studies are required to understand the metastasis development and predict the response to antitumor therapy for melanoma.